Bulfinch's Mythology: The Age of Fable - Bulfinch, Thomas, 1796-1867 (Salt Lake City, UT : Project Gutenberg, 2002)
"Bulfinch's Mythology: The Age of Fable" by Thomas Bulfinch is a collection published in 1867. This work retells classical myths, Arthurian legends, and medieval romances for English-speaking readers without knowledge of Latin or Greek. Bulfinch weaves together ancient tales with quotations from contemporary poets, creating a bridge between distant mythology and nineteenth-century literature. His accessible retellings$1 (Bdrawn primarily from Ovid but adapted to Victorian sensibilities$1 (Bdominated American classical education for nearly a century, helping general readers comprehend the mythological references pervading English literature and polite conversation. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Bulfinch%27s_Mythology
Release date is 2002-07-01
Produced by an anonymous Project Gutenberg volunteer
Keywords: Mythology, Classical; Mythology; Folklore -- Europe